Answer:
The function notation of the provided function is [tex]f(x)=6-5x[/tex].
Step-by-step explanation:
Consider the provided information.
We need to write [tex]5x+y =6[/tex] in function notation.
It is given that y is the dependent variable.
To write the above equation in function notation, solve the above equation for y and replace y with f(x).
[tex]5x+y =6[/tex]
Subtract 5x from both the sides.
[tex]5x-5x+y =6-5x[/tex]
[tex]y=6-5x[/tex]
Now replace y with f(x).
[tex]f(x)=6-5x[/tex]
Hence, the function notation of the provided function is [tex]f(x)=6-5x[/tex].